1985
DOI: 10.1200/jco.1985.3.11.1522
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of recombinant-derived interferon alpha in metastatic renal cell carcinoma.

Abstract: Fifty-six patients with metastatic renal cell carcinoma (RCC) were treated with recombinant DNA-derived interferon alpha (rIFN alpha A). The first 30 patients were randomized between doses of 2 X 10(6) U/m2 and 20 X 10(6) U/m2 intramuscularly daily. No complete (CR) or partial (PR) remissions were achieved in 15 patients receiving the low dose. In contrast, 27% of those receiving the high dose achieved CR or PR. Subsequently, 26 additional patients were given the high dose and achieved a 31% response rate. Rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
60
1
3

Year Published

1986
1986
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(64 citation statements)
references
References 19 publications
0
60
1
3
Order By: Relevance
“…Published clinical trials of INF alpha have reported response rates between 10-17% in renal cell carcinoma and melanoma (Hersey et al, 1985;Quesada et al, 1985). Phase II studies of IL-2 with or without LAK cells have reported tumour responses of 16-31 % in renal cell carcinoma and 14-26% in melanoma (Rosenberg et al, 1988;Fischer et al, 1988;Stahel et al, 1989;Dutcher et al, 1989;Bar et al, 1990), although at the cost of considerable acute toxicity.…”
mentioning
confidence: 99%
“…Published clinical trials of INF alpha have reported response rates between 10-17% in renal cell carcinoma and melanoma (Hersey et al, 1985;Quesada et al, 1985). Phase II studies of IL-2 with or without LAK cells have reported tumour responses of 16-31 % in renal cell carcinoma and 14-26% in melanoma (Rosenberg et al, 1988;Fischer et al, 1988;Stahel et al, 1989;Dutcher et al, 1989;Bar et al, 1990), although at the cost of considerable acute toxicity.…”
mentioning
confidence: 99%
“…Alpha-interferon (INF-ac) has also shown some therapeutic efficacy in patients with metastatic renal cell carcinoma, resulting in a 15% response rate (Quesada et al, 1985).…”
mentioning
confidence: 99%
“…Namely, the effective IFN concentration decreases because of the appearance of anti-IFN neutralizing antibodies, resulting in a reduced therapeutic effect. The production of anti-IFN neutralizing antibodies may be influenced by several factors, including dosing schedule (duration, dose, dosing time) and the use of an alternative IFN such as IFN-␣, IFN-␤, or IFN-␥ (17,39,42,46). One simple approach that can be used to prevent or overcome the production of anti-IFN antibodies is the use of a dosing schedule which reduces the level of production of anti-IFN antibodies.…”
Section: Discussionmentioning
confidence: 99%